Evaluation of a therapeutic education program for French family caregivers of elderly people suffering from major neurocognitive disorders: Preliminary study. Issue 4 (2nd October 2018) - Monfort, Emmanuel; Mayol, Antonio; Lissot, Clotilde; Couturier, Pascal
ABSTRACT: The pertinence of a therapeutic program of education has been studied with regard to carers of patients suffering from major neurocognitive disorders. The program, adapted to the needs expressed by the carers, consisted of three workshops with a view to supplying general information about the pathologies, specific information on behavioral disorders, and specific aids to identify and manage their emotional reactions. The results of this preliminary study show a moderate significant benefit to the level of anxiety in the participants, taking into account the specific expectations of the carers and bringing to light further needs.